Mapping the genes for susceptibility and response to Leishmania tropica in mouse - Sohrabi, Yahya; Havelková, Helena; Kobets, Tetyana; Šíma, Matyáš; Volkova, Valeriya; Grekov, Igor; Jarošíková, Taťána; Kurey, Iryna; Vojtíšková, Jarmila; Svobodová, Milena; Demant, Peter; Lipoldová, Marie (PLoS neglected tropical diseases, 2013)
BACKGROUND: L. tropica can cause both cutaneous and visceral leishmaniasis in humans. Although the L. tropica-induced cutaneous disease has been long known, its potential to visceralize in humans was recognized only recently. As nothing is known about the genetics of host responses to this infection and their clinical impact, we developed an informative animal model. We described previously that the recombinant congenic strain CcS-16 carrying 12.5% genes from the resistant parental strain STS/A and 87.5% genes from the susceptible strain BALB/c is more susceptible to L. tropica than BALB/c. We used these strains to map and functionally characterize the gene-loci regulating the immune responses and pathology. METHODS: We analyzed genetics of response to L. tropica in infected F2 hybrids between BALB/c×CcS-16. CcS-16 strain carries STS-derived segments on nine chromosomes. We genotyped these segments in the F2 hybrid mice and tested their linkage with pathological changes and systemic immune responses. PRINCIPAL FINDINGS: We mapped 8 Ltr (Leishmania tropica response) loci. Four loci (Ltr2, Ltr3, Ltr6 and Ltr8) exhibit independent responses to L. tropica, while Ltr1, Ltr4, Ltr5 and Ltr7 were detected only in gene-gene interactions with other Ltr loci. Ltr3 exhibits the recently discovered phenomenon of transgenerational parental effect on parasite numbers in spleen. The most precise mapping (4.07 Mb) was achieved for Ltr1 (chr.2), which controls parasite numbers in lymph nodes. Five Ltr loci co-localize with loci controlling susceptibility to L. major, three are likely L. tropica specific. Individual Ltr loci affect different subsets of responses, exhibit organ specific effects and a separate control of parasite load and organ pathology. CONCLUSION: We present the first identification of genetic loci controlling susceptibility to L. tropica. The different combinations of alleles controlling various symptoms of the disease likely co-determine different manifestations of disease induced by the same pathogen in individual mice.
Keywords: leishmanióza kožní; Disease Models, Animal; Genetic Loci; myši; Leishmaniasis, Cutaneous; modely nemocí na zvířatech; Host-Pathogen Interactions; Chromosome Mapping; Animals; genetické lokusy; Disease Susceptibility; náchylnost k nemoci; Female; ženské pohlaví; Mice; mapování chromozomů; interakce hostitele a patogenu; zvířata